2016
DOI: 10.1111/hequ.12109
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Academic Performance of Non‐native English‐Speaking Students: the Contribution of Pre‐sessional English Language Programmes

Abstract: There is an established, if weak, inverse relationship between levels of English language proficiency and academic performance in higher education. In response, higher education institutions (HEIs) insist upon minimum entry requirements concerning language for international applicants. Many HEIs now also offer pre‐sessional English courses to bring applicants up to the designated language requirement. This paper revisits the research into language proficiency and academic performance using data on all full‐tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 13 publications
0
33
0
Order By: Relevance
“…Through their investigation they supported an IELTS 6.0 as a minimum threshold level for success. In a recent UK‐based IELTS paper with a large sample of 611 students, Thorpe, Snell, Davey‐Evans, and Talman () concluded that ‘both undergraduate and postgraduate NNES [non‐native English speakers] underperformed in GPA terms compared to their English‐speaking counterparts’ (p. 28) irrespective of IELTS score. However, NNES students who began study with the required IELTS entrance score did significantly better than students needing further English preparation prior to beginning their programmes of study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Through their investigation they supported an IELTS 6.0 as a minimum threshold level for success. In a recent UK‐based IELTS paper with a large sample of 611 students, Thorpe, Snell, Davey‐Evans, and Talman () concluded that ‘both undergraduate and postgraduate NNES [non‐native English speakers] underperformed in GPA terms compared to their English‐speaking counterparts’ (p. 28) irrespective of IELTS score. However, NNES students who began study with the required IELTS entrance score did significantly better than students needing further English preparation prior to beginning their programmes of study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Analysis of the literature revealed 11 studies founded on the quantitative language programme evaluation tradition. Among this group, three sub‐designs were identified; studies which tracked students' progress from PSP to degree by documenting their assessed marks/completion rates (Allwright & Banerjee, ; Millar, ; Atherton, ; Martala, ; Ridley, ; Lloyd‐Jones et al , ), studies describing or measuring students' language development over a PSP (Archibald, ; Green, ; Issitt, ), and those investigating the nature of the relationship between PSP outcomes and academic results (Ushioda & Harsch, ; Thorpe et al , ). Qualitative research into PSP effectiveness was noticeably less common (five studies).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Thorpe et al 's. () recent study stands out as a rare example of researchers establishing how students who are admitted via pre‐sessional programmes compare academically with their colleagues who meet the linguistic entry requirements, as well as with native‐speaking students. Utilising data from the entire cohort of full‐time students at a university in southern England (including 4,342 NNES students) the researchers developed a regression model, with PSP completion being a key independent variable investigated.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations